Relationship of Self Effectiveness with Compliance of Eating Medicines for Pulmonary Tuberculosis Sufferers - Silaban, Jojor; Harahap, Solihuddin; Silaban, Verawaty Fitrinelda (GLOBAL HEALTH SCIENCE GROUP, 2024)
Self-efficiency and attitude in order to be able to adapt to self-changing in the sense of obedience to medication. Compliance in taking anti-tuberculosis drugs is crucial in the healing process of pulmonary tuberculosis. In undergoing long-term treatment, patient compliance is highly required to know the patient's attitude and behavior to the treatment program given by the health officer. In order to have medication compliance, the patient must have high self-efficiency.Method : The research method is an observational analytical with cross sectional design approach involving 51 respondents who are undergoing treatment in the Puskesmas Beruh Work Area. Sampling technique is total sampling. The data collection technique in this research is by using an angket or a questionnaire. Data analysis using a chi square test with a fertility rate of 0.05.Result : The results of the research show that health workers in the area of Puskesmas Batang Beruh work should pay attention to the improvement in the effectiveness of patients with pulmonary tuberculosis, with a p value of 0,000. The results of the bi-variation test showed a significant correlation between self-effectiveness and drug consistency, with a high-grade majority of 59.18% and a higher-category mayority of 75.51%.